2020
DOI: 10.1002/mar.21343
|View full text |Cite
|
Sign up to set email alerts
|

Consumer relationship fading

Abstract: This paper explores the phenomenon of consumer relationship fading with a series of three adjacent studies. Analyzing two longitudinal behavioral datasets, Study 1 shows that about 1/3 of the relationships could be described as fading. Drawing on prior work in the marriage disaffection literature, Study 2 defines relationship fading for the consumer marketing context as a process of gradual decline in consumers' intention to continue their relationship with a brand, generally manifested in negative feelings to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 115 publications
0
18
0
Order By: Relevance
“…An FMRI study on consumers' simulated brains showed activations in the brain areas associated with negative emotions when the consumers looked at products of weak and unfamiliar brands, whereas positive emotions were evoked when strong and familiar brands were shown (Esch et al., 2012). Finally, it has been observed that negative emotions peak in a CBR before the relationship eventually fades away (Evanschitzky et al., 2020).…”
Section: Overviewmentioning
confidence: 99%
“…An FMRI study on consumers' simulated brains showed activations in the brain areas associated with negative emotions when the consumers looked at products of weak and unfamiliar brands, whereas positive emotions were evoked when strong and familiar brands were shown (Esch et al., 2012). Finally, it has been observed that negative emotions peak in a CBR before the relationship eventually fades away (Evanschitzky et al., 2020).…”
Section: Overviewmentioning
confidence: 99%
“…Although most researchers and practitioners recognize the value of relationship marketing (RM), the effectiveness of RM can depend on several factors such as prior customer-brand experiences (Fournier, 1998), risk avoidance (Gu et al, 2017), relationship avoidance (Noble and Phillips, 2004;Grégoire et al, 2009;Ashley et al, 2011;Ha and Lee, 2012;Ha, 2015Ha, , 2017, relationship fading (Evanschitzky et al, 2020), or anticonsumption behavior (Lee et al, 2009). This section starts with a summary of prior experiences that are well documented in the relationship marketing literature and subsequently presents a review of research related to digital relationship termination behavior.…”
Section: Background Of Termination Behaviorsmentioning
confidence: 99%
“…An economic benefit is another example. If relationship maintenance becomes more difficult, users may consider abandoning the relationship (Evanschitzky et al, 2020). In sum, these three loss categories that constitute relationship termination essentially should reflect the important role of personal loss in the relational process.…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedonic adaptation threatens the consumer experience (Evanschitzky et al, 2020; He, Chen, & Alden, 2016) and usually starts almost immediately after product acquisition (Richins, 2013). Yet, limited work in marketing identifies the factors that moderate this trend.…”
Section: Introductionmentioning
confidence: 99%